Analysis of Bearing Current in Doubly-fed Induction Generator for Wind Power - DENG Fanglin; WANG Jianliang; KUANG Jinyuan; TANG Jianping; CHEN Shichao (Kongzhi Yu Xinxi Jishu)
As the rotor of doubly-fed induction generator (DFIG) for wind power is supplied by PWM voltage source inverter, bearing damage caused by bearing current is very common.Through analyzing the generation mechanism of common mode voltage, it presented a high frequency equivalent circuit model of DFIG,analyzed the characteristics of various bearing currents and their flow paths,and summarized their preventive measures and basic design principles.